Augmented Reality Tools in Physics Training at Higher Technical Educational Institutions (Pedagogy of Higher and Secondary Education, 2018)
Hruntova T. V., Yechkalo YU. V., Stryuk A. M. and Pikilʹnyak A. V. Augmented Reality Tools in Physics Training at Higher Technical Educational Institutions.Research goal: the research is aimed at theoretical substantiation of applying the augmented reality technology and its peculiarities at higher technical educational institutions. Research objectives: the research is to solve the problems of determining the role and place of the technology in the educational process and its possible application to physics training. Object of research: teaching physics to students of higher technical educational institutions. Subject of research: the augmented reality technology as a component of the training process at higher educational institutions. Research methods used: theoretical methods include analysis of scientific and methodological literature; empirical methods include studying and observation of the training process. Research results: analysis of scientific publications allows defining the notion of augmented reality; application of augmented reality objects during laboratory practical works on physics is suggested. Main conclusions. introduction of the augmented reality technology in thetraining process at higher technical educational institutions increases learning efficiency, facilitates students’ training and cognitive activities, improves the quality of knowledge acquisition, provokes interest in a subject, promotesdevelopment of research skills and a future specialist’s competent personality.
Keywords: mobile learning technology; augmented reality technology; training at university,; a physics laboratory practicum